Sportininku širdies nuovargio metaboliniai rodikliai: apžvalga - Gunina, L.; Bezuglaya, V. (Sporto Mokslas-Sport Science, 2017)
Both specific and nonspecific metabolic transformations, occurring in the body of athlete under intensive and prolonged physical loads, have been characterized in the review paper. It has been emphasized that oxidative stress, which belongs to general pathogenic factors of further myocardium pathology formation, and load induced hypoxia, which is later associated with tissue hypoxia of metabolic origin, represent the initial link of subsequent homeostatic balance changes. Changes in the activity of creatine phosphokinase-MB fraction, content of cardiac troponins I and T as well as terminal natriuretic peptides are referred to specific markers of myocardium strain. Wider range of myocardium strain nonspecific markers includes both alterations of lipid metabolism and numerous, oxidative stress mediated, metabolic changes at the level of cellular and subcellular membranes of cardiomyocytes, followed by changes in the activity of membrane-bound enzymes and lysosomal proteinase ejection first into extracellular matrix and then - into circulatory bed as well as erythrocyte membranes and their ATP content that are accompanied by deterioration of blood oxygen transport function. The above mentioned negatively influences myocardial contractility and leads to the development of hypertrophic cardiomyopathy. Identification of the markers of athlete heart strain allows timely to be corrected by pharmacological means, aimed at normalization of metabolic disorders and prevention of myocardial hypertrophy, which is the major cause of sudden coronary death among athletes.